2014
DOI: 10.1200/jop.2013.001268
|View full text |Cite
|
Sign up to set email alerts
|

Provider-Based Research Networks Demonstrate Greater Hospice Use for Minority Patients With Lung Cancer

Abstract: Minority patients with lung cancer receiving treatment in cancer-focused PBRN- affiliated practices have greater hospice enrollment than those treated in academic and community practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…PBRNs are a recently emerging approach in public health settings with growing utility [ 26 – 29 ]. Increased research related capacity of PBRNs to enhance services [ 30 ] and improve data and surveillance [ 31 ] has also been demonstrated with clinical practice PBRNs. The use of PBRNs to support quality improvement in local public health agencies is an example of enhanced research related capacity to improve services, albeit not research in itself.…”
Section: Methodsmentioning
confidence: 99%
“…PBRNs are a recently emerging approach in public health settings with growing utility [ 26 – 29 ]. Increased research related capacity of PBRNs to enhance services [ 30 ] and improve data and surveillance [ 31 ] has also been demonstrated with clinical practice PBRNs. The use of PBRNs to support quality improvement in local public health agencies is an example of enhanced research related capacity to improve services, albeit not research in itself.…”
Section: Methodsmentioning
confidence: 99%
“…Networks may offset these barriers by creating administrative links and referral access, as well as access to expert advice. In fact, research has shown that community practices affiliated with a medical school or cancer research network provide better access to evidence-based care than non-affiliated centers [26][27][28]. This includes better access to treatments and clinical trials [26,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…1 Oncological networks often contain a structured care pathway and multidisciplinary tumor boards aiming to reduce practice variation, provide educational opportunities for all specialists involved, and reduce individual physician biases. 2,3 Interhospital collaboration also contributes to improved access to evidence-based health care, [4][5][6] new treatment options, and clinical studies. 7,8 Previously, we have demonstrated the impact of a regional network on referral patterns in patients with thyroid cancer.…”
mentioning
confidence: 99%